2017
DOI: 10.1002/pmic.201700103
|View full text |Cite
|
Sign up to set email alerts
|

Motile hepatocellular carcinoma cells preferentially secret sugar metabolism regulatory proteins via exosomes

Abstract: Exosomes are deliverers of critically functional proteins, capable of transforming target cells in numerous cancers, including hepatocellular carcinoma (HCC). We hypothesize that the motility of HCC cells can be featured by comparative proteome of exosomes. Hence, we performed the super-SILAC-based MS analysis on the exosomes secreted by three human HCC cell lines, including the non-motile Hep3B cell, and the motile 97H and LM3 cells. More than 1400 exosomal proteins were confidently quantified in each MS anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Indeed, it has been shown that glycolytic enzymes found within prostate-derived EVs are functional inside the vesicles and can generate ATP upon incubation with their substrates (87) and that this process is required for EV uptake (88). As glycolytic enzymes were found to be more abundant in the EVs secreted by aggressive cancer cells, these vesicles may be more efficiently taken up by recipient cells, leading to an increased transfer of material (86). Nevertheless, the presence of glycolytic enzymes in EVs is not necessarily associated with a functional transfer.…”
Section: Evs and Metabolism (Excluding Fa-related Pathways) Among Thementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that glycolytic enzymes found within prostate-derived EVs are functional inside the vesicles and can generate ATP upon incubation with their substrates (87) and that this process is required for EV uptake (88). As glycolytic enzymes were found to be more abundant in the EVs secreted by aggressive cancer cells, these vesicles may be more efficiently taken up by recipient cells, leading to an increased transfer of material (86). Nevertheless, the presence of glycolytic enzymes in EVs is not necessarily associated with a functional transfer.…”
Section: Evs and Metabolism (Excluding Fa-related Pathways) Among Thementioning
confidence: 99%
“…Indeed, in a study aiming to compare the exoproteome of a nonaggressive vs an aggressive hepatocellular carcinoma cell line, aggressive cell-derived EVs are enriched in sugar-related metabolic pathways, namely glycolysis, gluconeogenesis and pentose phosphate pathways (86). Hence, transfer of glycolytic enzymes between cancer cells may impact the metabolism of recipient cells.…”
Section: Evs and Metabolism (Excluding Fa-related Pathways) Among Thementioning
confidence: 99%
“…In-Gel Digestion [33][34][35][36][37] FASP [38,39] Combined method In-Gel Digestion [28,35,36,[40][41][42][43][44][45][46][47][48][49][50][51] In-Sol Digestion [52][53][54] FASP [51,[55][56][57][58][59] Plasma/ Serum Ultracentrifuge In-Sol Digestion [60] FASP [56] Combined method In-Gel Digestion [43] In-Sol Digestion [44,52] FASP [51,57,58] secreted by MCF7, 30 proteins have been known to participate in breast cancer growth, metastasis, and chemoresistance. The most abundant MDA-MD-231 derived exosomal protein is β-actin, which is frequently used as a housekeeping gene in the exosome.…”
Section: Cell Ultracentrifugementioning
confidence: 99%
“…Differential ultracentrifugation is considered the gold standard method for purification of exosomes and most of the studies have applied this technique for isolating HCC-derived exosomes [27,28] . However, depending on the starting material and downstream applications, other methods for the purification and enrichment of HCC-derived exosomes have also been used such as ultrafiltration, size exclusion chromatography (SEC) or the ExoQuick TC method [19,29] .…”
Section: Isolation and Identification Methods Of Hcc-derived Exosomesmentioning
confidence: 99%
“…Motile behaviour in MIHA cells was triggered by activation of PI3K/AKT and MAPK signalling pathways which in turn increased secretion of active matrix metalloproteinase, MMP-2 and MMP-9 [56] . A comparative proteome analysis of exosomes from the non-motile Hep3B cell, and the motile 97H and LM3 cells found the motile HCC cells to secrete more sugar metabolism regulatory proteins via exosomes in the tumour microenvironment [28] . The ability of exosomes to modulate the motile ability of tumour cells was tested by comparing protein profiles of cell lines with distinct metastatic potential.…”
Section: Modulation Of Hcc Tumour Growth and Metastasismentioning
confidence: 99%